Um estudo sobre pontos extremos em espaços de Banach - Ramon Gustavo de Melo (2019)
In this work are exhibited topological and geometric facts related to two Banach spaces and its topological dual spaces. Moreover, the Krein-Milman Theorem and other statement are applied in order to get two profits. The first of them is the finding of the set of extreme points of the closed ball B[0, 1] of the dual space of three simple Banach spaces. The second profit, in its turn, consists in a proof for the Banach-Stone Theorem